Weak and Straddling Secondary Nicotinic Synapses Can Drive Firing in Rat Sympathetic Neurons and Thereby Contribute to Ganglionic Amplification - Rimmer, Katrina; Horn, John P. (Frontiers in Neurology, 2010)
Interactions between nicotinic EPSPs critically determine whether paravertebral sympathetic ganglia behave as simple synaptic relays or as integrative centers that amplify preganglionic activity. Synaptic connectivity in this system is characterized by an n + 1 pattern of convergence, where each ganglion cell receives one very strong primary input and a variable number (n) of weak secondary inputs that are subthreshold in strength. To test whether pairs of secondary nicotinic EPSPs can summate to fire action potentials and thus mediate ganglionic gain in the rat superior cervical ganglion, we recorded intracellularly at 34° C and used graded presynaptic stimulation to isolate individual secondary synapses. Weak EPSPs in 40 of 53 neurons had amplitudes of 0.5 – 7 mV (mean 3.5 ± 0.3 mV). EPSPs evoked by paired pulse stimulation were either depressing (n = 10), facilitating (n = 9) or borderline (n = 10). In 15 of 29 cells, pairs of weak secondary EPSPs initiated spikes when elicited within a temporal window <20 ms, irrespective of EPSP amplitude or paired pulse response type. In 6 other neurons, we observed novel secondary EPSPs that were strong enough to straddle spike threshold without summation. At stimulus rates <1 Hz straddling EPSPs appeared suprathreshold in strength. However, their limited ability to drive firing could be blocked by the afterhypolarization following an action potential. When viewed in a computational context, these findings support the concept that weak and straddling secondary nicotinic synapses enable mammalian sympathetic ganglia to behave as use-dependent amplifiers of preganglionic activity.